(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of combining fascia iliaca block and low-dose spinal anesthesia for hip replacement surgery in frail elderly patients at Friendship Hospital from January 2025 to June 2025. Methods: An interventional, uncontrolled, descriptive case series study. Results: A total of 15 elderly patients (≥ 80 years old) with frailty (Fried score ≥ 3/5 points) who were indicated for hip replacement surgery (either partial or total) due to trauma were selected for the study. The success rate of the technique was 93.3%; the incidence of severe hypotension was 6.7%. The ANI at the time of skin incision was 84.2 ± 10.5 points; the ANI at the time of skin closure was 80.5 ± 9.2 points. The need for emergency analgesic medication during surgery was 6,7%. Complete lower limb motor blockade occurred in 93,3% of cases. The duration of postoperative analgesia was 8.1 ± 1.5 hours. Conclusion: The combination of fascia iliaca block and low-dose spinal anesthesia for hip replacement surgery in frail elderly patients shows a high success rate, reduces intraoperative severe hypotension, and provides effective postoperative pain relief.